2018
DOI: 10.1021/acs.est.8b03217
|View full text |Cite
|
Sign up to set email alerts
|

An Estimate of Natural Gas Methane Emissions from California Homes

Abstract: We estimate postmeter methane (CH) emissions from California's residential natural gas (NG) system using measurements and analysis from a sample of homes and appliances. Quiescent whole-house emissions (i.e., pipe leaks and pilot lights) were measured using a mass balance method in 75 California homes, while CH to CO emission ratios were measured for steady operation of individual combustion appliances and, separately, for transient operation of three tankless water heaters. Measured quiescent whole-house emis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
78
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(83 citation statements)
references
References 10 publications
5
78
0
Order By: Relevance
“…In bottom-up studies of residential and commercial buildings, appliances and furnaces were reported to have loss rates of 0.1 to 0.3% of consumed gas (20,21,23); transmission (compressor stations, etc.) is estimated to have a loss rate of 0.2% (4).…”
Section: Resultsmentioning
confidence: 99%
“…In bottom-up studies of residential and commercial buildings, appliances and furnaces were reported to have loss rates of 0.1 to 0.3% of consumed gas (20,21,23); transmission (compressor stations, etc.) is estimated to have a loss rate of 0.2% (4).…”
Section: Resultsmentioning
confidence: 99%
“…The study also reaffirmed existing theories that a fraction of variability in enhancement and emissions in the basin is correlated with air temperature and energy demand. However, this has not been conclusively established in either this study or previous studies and would require detailed investigation, that is, studies that can isolate this process at the level of households (e.g., Fischer et al, 2018). Similarly, identification of the impact of episodic processes and apportioning of fluxes to specific facilities remained elusive due to the density and coverage provided by the current in situ network, indicating a requirement for a denser network, the establishment of which should be guided by pseudo data-inverse modeling studies that account for atmospheric transport (e.g., Pillai et al, 2012) in informing fluxes at an in situ site from near-and farfield sources.…”
Section: Discussionmentioning
confidence: 61%
“…However, this has not been conclusively established in either this study or previous studies and would require detailed investigation, that is, studies that can isolate this process at the level of households (e.g., Fischer et al, 2018). However, this has not been conclusively established in either this study or previous studies and would require detailed investigation, that is, studies that can isolate this process at the level of households (e.g., Fischer et al, 2018).…”
Section: Discussionmentioning
confidence: 71%
“…There is increasing evidence that the probability density functions for CH 4 emissions have a long tail, characterized by a small number of emitters with very large emissions, perhaps due to malfunctioning equipment or improper operating conditions (Zavala-Araiza et al, 2015). This will require a concerted measurement campaign examining large numbers of emitters (thousands) under actual operating conditions targeting residential, commercial, and industrial sectors (Fischer et al, 2018).…”
Section: Discussionmentioning
confidence: 99%